2015
DOI: 10.1021/acs.jpcc.5b09638
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Etching on Electron–Hole Recombination in Sr-Doped NaTaO3 Photocatalysts

Abstract: Sodium tantalate (NaTaO 3 ) photocatalysts doped with Sr 2+ produce core− shell-structured NaTaO 3 −SrSr 1/3 Ta 2/3 O 3 solid solutions able to split water efficiently, when prepared via the solid-state method. In this study, the photocatalysts were chemically etched to examine the different roles of the core and shell with respect to the recombination of electrons and holes. Under excitation by Hg−Xe lamp irradiation, the steady-state population of electrons in the core−shell-structured photocatalyst with a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 39 publications
3
28
0
Order By: Relevance
“…It has been previously reported that Sr-doped NaTaO 3 easily forms Sr-rich shells covering Sr-poor cores and that electron–hole recombination is restricted during photoirradiation, enhancing photocatalytic activity. 41,42 In the current work, a Sr-rich shell with a Sr-poor core is also observed when the molar ratio of NaCl/KCl is less than 50%. Conversely, a Sr-poor shell with a Sr-rich core is formed when the molar ratio of NaCl/KCl is higher than 50% (Table 2).…”
Section: Resultssupporting
confidence: 57%
“…It has been previously reported that Sr-doped NaTaO 3 easily forms Sr-rich shells covering Sr-poor cores and that electron–hole recombination is restricted during photoirradiation, enhancing photocatalytic activity. 41,42 In the current work, a Sr-rich shell with a Sr-poor core is also observed when the molar ratio of NaCl/KCl is less than 50%. Conversely, a Sr-poor shell with a Sr-rich core is formed when the molar ratio of NaCl/KCl is higher than 50% (Table 2).…”
Section: Resultssupporting
confidence: 57%
“…An et al . proposed that the recombination rate was controlled by the concentration gradient of Sr cations at the B site in the photocatalyst particles, not by the absolute concentration of Sr cations at the B site.…”
Section: Nanoscale Architectures For Driving Electron Excitationmentioning
confidence: 94%
“…They chemically etched Sr‐doped photocatalysts and evaluated the steady‐state population of excited electrons in the etched photocatalysts. The observed response to etching time supported the hypothesis …”
Section: Nanoscale Architectures For Driving Electron Excitationmentioning
confidence: 99%
“…Onishi'group proposed that the gradient distribution from Sr-rich surface to Sr-poor core is spontaneously generated by diffusion controlled solid-state reaction during the preparation of NaTaO 3 photocatalyst. 16 This induced BIEF drives the separation of excited electrons from complementary holes, thereby restricting recombination. Yu et al built a suitable band structure by gradient doping carbon-ring in CN structure.…”
Section: Introductionmentioning
confidence: 99%